A guide to planning and support for individuals who are deafblind - McInnes, J. M. (John M.) (Book collections on Project MUSE., 1999)
In this collection of leading experts in the field address the problems of parents, intervenors, and professionals who work with people who have been dead-blind since birth or from a very early age.